The Influence of Intellectual Capital on Return on Asset on BUMN Bank Listed on BEI 2015-2022 - Suhadi, Ilyas Alfian; Kahfi, Muhammad Ismail (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this research is to determine the components of intellectual capital, namely Value-Added Human Capital (VAHU), Value Added Structural Capital (STVA), and Value-Added Capital Employed (VACA) in influencing Return on Assets. This research is quantitative and uses secondary data. The population of this research is state-owned companies in the banking sector registered on the IDX in 2015-2022. The number of samples studied was 32 samples. This research uses descriptive statistics, classical assumption testing, and hypothesis testing. The results of this research show that VACA, VAHU, and STVA together or simultaneously have a significant influence on Return on Assets (ROA). All independent variables VAHU, STVA, and VACE can contribute 68.6% of ROA. Then the results of the partial test, VAHU partially has a significant positive effect on ROA, VACE partially has a significant positive effect on ROA but STVA partially gives positive results but is not significant on ROA.